Pragmatics of Educational Discourse in the Work of Abu al-‘Abbas al-Fayyumi (d. 770 AH) Through His Lexicon Al-Misbah al-Munir - bouchana, omar (El Omda in Linguistics and Discourse Analysis, 2018)
The study of pragmatics covers many diverse fields, particularly those related to the linguistic aspect. It has a close connection with general linguistics, functional grammar, and semantics, in addition to social, psychological, and educational linguistics, as well as text linguistics and discourse analysis. All of this aims to explore the ways meaning is conveyed and communication occurs between language users, and goes further to examine how the element of influence is created, enabling language to affect human behavior, attitudes, and opinions through actual linguistic performance.